2019
DOI: 10.12928/telkomnika.v17i3.10144
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle detection using background subtraction and clustering algorithms

Abstract: Traffic congestion has raised worldwide as a result of growing motorization, urbanization, and population. In fact, congestion reduces the efficiency of transportation infrastructure usage and increases travel time, air pollutions as well as fuel consumption. Then, Intelligent Transportation System (ITS) comes as a solution of this problem by implementing information technology and communications networks. One classical option of Intelligent Transportation Systems is video camera technology. Particularly, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The Gaussian noise is removed to the Bf(r, c) by Gaussian filter which makes use of (k×k) size aperture selected through experimental results as (5). It should be observed that median filters and Gaussian filters have a point view; the center location values may not derive (not originate) from the pixel values in the source frame when the median filter's location values are derived from the original pixel values of the source frame.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…The Gaussian noise is removed to the Bf(r, c) by Gaussian filter which makes use of (k×k) size aperture selected through experimental results as (5). It should be observed that median filters and Gaussian filters have a point view; the center location values may not derive (not originate) from the pixel values in the source frame when the median filter's location values are derived from the original pixel values of the source frame.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…In order to determine the accuracy, we use the confusion matrix as in Table 1 [22]. The formula for calculating the accuracy is shown by (3).…”
Section: Research Methods 21 Fully Convolutional Network: U-net With Transfer Learningmentioning
confidence: 99%
“…The aim is to get the best model that could recognize TELKOMNIKA Telecommun Comput El Control  UNet-VGG16 with transfer learning for MRI-based brain tumor … (Anindya Apriliyanti Pravitasari) 1311 the tumor area more precisely. The previous studies use the clustering as the basis of segmentation are performed by [2] which uses the genetic algorithm and [3] which employ fuzzy clustering, Otsu method and K-means cluster to segment the vehicle image. The model-based clustering is performed by [4][5][6] in the form of a Finite mixture model to segment the MRI brain tumor image.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, VCA is of high importance in subway stations to detect dangerous situations and secure the areas [3]. Transportation systems rely on VCA to ensure passengers security, vehicle control, and better tracking methods [4]. Furthermore, video analysis is used to detect underwater objects [5].…”
Section: Introductionmentioning
confidence: 99%